Prevalence and correlates of sexual behaviors among Karen villagers in northern Thailand - Eiko Kobori (2018)
A cross-sectional survey was conducted in two mountainous villages of the Karen, a major ethnic minority in Thailand. The participants were 566 villagers aged 15-54 years (371 in Village A, 195 in Village B; response rate=81.9%). Premarital/extramarital sex was experienced by 10-20% of the sexually active respondents and sex with a female sex worker (FSW) by 12.6% of males. Premarital sex was independently associated with being a Christian and occupational experience in town; extramarital sex was associated with Village A and drug use; sex with a FSW was associated with being unmarried, a nonfarmer, and occupational experience in town. Approximately 80% of the married participants never used a condom with their spouse, and nearly one-third never did so with a boy/girlfriend or a FSW. A history of sexually transmitted infections (STIs) was associated with sex with a FSW. These findings suggest that nontraditional sexual practices are prevalent and could potentially threaten Karen communities with the spread of HIV. © 2006 Springer Science+Business Media, LLC.